D10 Pharmacodynamic Biomarkers For Selisistat: The Paddington Project. (17th September 2014) - Pollio, G; Massai, L; Diamanti, D; Magnoni, L; Westerberg, G; Farmer, RE; Frost, C; Tabrizi, SJ; Landwehrmeyer, GB; Thomas, R
Abstract : Background: Siena Biotech is developing a highly selective SIRT1 inhibitor, selisistat, as a potentially disease-modifying therapy for Huntington's disease. Selisistat has shown to ameliorate HD phenotypes in HD preclinical models, from cells expressing mutant huntingtin to transgenic Drosophila and R6/2 mice before entering the clinical trials. Selisistat recently completed the Phase II Study, assessing safety and tolerability in HD patients. Aim: Evaluate possible selisistat pharmacodynamic biomarkers to support further clinical progression. Within the EC funded project PADDINGTON, a transcriptional profile and huntingtin protein levels were evaluated in biological samples from HD patients treated with placebo or selisistat at different doses. Methods: HD patients were randomised to receive different doses of selisistat or placebo. Serial blood sampling was collected at different time points after selisistat administration. Peripheral blood mononuclear cells (PBMCs) were employed to detect HTT protein levels by a validated ELISA bioassay. Whole blood samples were analysed through RT-qPCR to validate a previous identified transcriptional signature. Results: Four transcripts were found specifically modulated by selisistat in whole blood samples, confirming the transcriptional signature. Moreover, the ELISA in PBMCs has proven to reliably measure of circulating HTT despite the low protein levels and high individual variability. Conclusions: The quantisation of circulating HTT levels as well as gene expression evaluation represents a promising avenue towards monitoring disease progression and therapeutic interventions. Additionally, transcriptional signatures could be useful to draw hypotheses for target engagement and mechanism of action through the pathway analysis of the modulated genes. Final results for both investigations will be presented.